A decade of sustained selection pressure on two surface sites of the VP1 protein of Enterovirus A71 suggests that immune evasion may be an indirect driver for virulence - Roberts, Ryan; Yee, Isabel Pin Tsin *; Mujawar, Shama *; Lahiri, Chandrajit *; Poh, Chit Laa *; Gatherer, Derek (Nature Research, 2019)
Enterovirus A71 (EV-A71) is an emerging pathogen in the Enterovirus A species group. EV-A71 causes hand, foot and mouth disease (HFMD), with virulent variants exhibiting polio-like acute faccid paralysis and other central nervous system manifestations. We analysed all enterovirus A71 complete genomes with collection dates from 2008 to mid-2018. All sub-genotypes exhibit a strong molecular clock with omega (dN/dS) suggesting strong purifying selection. In sub-genotypes B5 and C4, positive selection can be detected at two surface sites on the VP1 protein, also detected in positive selection studies performed prior to 2008. Toggling of a limited repertoire of amino acids at these positively selected residues over the last decade suggests that EV-A71 may be undergoing a sustained frequencydependent selection process for immune evasion, raising issues for vaccine development. These same sites have also been previously implicated in virus-host binding and strain-associated severity of HFMD, suggesting that immune evasion may be an indirect driver for virulence (154 words).